2018
DOI: 10.1002/cpdd.439
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Pharmacokinetics, Safety, and Preliminary Efficacy of Topical AhR Agonist Tapinarof: Results of a Phase 1 Study

Abstract: Tapinarof cream is a novel topical nonsteroidal agent that represents a unique class of anti-inflammatory molecules targeting the aryl hydrocarbon receptor. Study 201851 was an open-label, 2-cohort sequential study that assessed the systemic pharmacokinetics, safety, and efficacy of tapinarof in adults with moderate to severe atopic dermatitis. A total of 11 participants were enrolled: 5 received 2% cream, and 6 received 1% cream. Tapinarof was systemically absorbed, and measurable amounts were detected in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Coal tar, glyteer, and tapinarof could feasibly upregulate the EDC molecules, including FLG, IVL, and hornerin, via AHR activation and exert their antioxidative function via NRF2 activation [25,31,152]. Recent clinical trials of topical tapinarof have proved its efficacy for AD compared with placebo control [150,151,156]. Medicinal AHR/NRF2 dual agonists can restore the IL-4/IL-13-STAT6-induced downregulation of FLG, LOR, and IVL expression.…”
Section: Medicinal Use Of Ahr/nrf2 Dual Activators For Admentioning
confidence: 99%
“…Coal tar, glyteer, and tapinarof could feasibly upregulate the EDC molecules, including FLG, IVL, and hornerin, via AHR activation and exert their antioxidative function via NRF2 activation [25,31,152]. Recent clinical trials of topical tapinarof have proved its efficacy for AD compared with placebo control [150,151,156]. Medicinal AHR/NRF2 dual agonists can restore the IL-4/IL-13-STAT6-induced downregulation of FLG, LOR, and IVL expression.…”
Section: Medicinal Use Of Ahr/nrf2 Dual Activators For Admentioning
confidence: 99%
“…Tapinarof is a high affinity AHR ligand with antioxidative activity via NRF2 activation and a ROS-scavenging structure [102] (Figure 1). Tapinarof has gained increased attention because its topical application is efficacious for patients with AD in clinical trials [21,100,104]. Tapinarof activates the AHR/CYP1A1 axis and augments the expression of filaggrin and involucrin [102].…”
Section: Ahr and Atopic Dermatitismentioning
confidence: 99%
“…Tapinarof activates the AHR/CYP1A1 axis and augments the expression of filaggrin and involucrin [102]. Even in barrier-disrupted AD patients, systemic absorption of topical tapinarof is limited and likely decreases during the treatment course in parallel with treatment success that restores the barrier dysfunction [104]. In general, topical tapinarof is tolerable but frequent adverse events include headaches and folliculitis [104].…”
Section: Ahr and Atopic Dermatitismentioning
confidence: 99%
“…Tapinarof activates both AHR and NRF2, up-regulates the expression of FLG and IVL, and exhibits antioxidative activity [209,210]. Double-blind clinical trials have shown that topical tapinarof is efficacious for treating patients with AD compared with placebo [211][212][213].…”
Section: Mechanisms Of Action Of Pharmaceutical Agents In Admentioning
confidence: 99%